Artificial Intelligence in Dentistry: An Umbrella Review of Systematic Reviews (Academia Journal of Medicine, 2026)
Background: Artificial intelligence (AI) has rapidly emerged as a transformative technology  in healthcare, including dentistry. AI-driven systems are increasingly being used for diagnostic  imaging, treatment planning, and predictive analysis. Numerous systematic reviews have  evaluated the role of AI across various dental specialties. However, a comprehensive  synthesis of these reviews is lacking.Objective: This umbrella review aims to summarize  and critically analyze the evidence from systematic reviews evaluating the applications and  outcomes of artificial intelligence in dentistry.Methods: Electronic databases including  PubMed, Scopus, and Google Scholar were searched for systematic reviews assessing  artificial intelligence applications in dentistry. Reviews published in English that evaluated  clinical, diagnostic, or educational applications of AI were included. Data extraction  included author details, year of publication, focus area, and key findings. Results: A total  of eight systematic reviews were included. The evidence suggests that AI is widely applied  in dental radiology, orthodontics, pediatric dentistry, and implantology. AI-based systems  demonstrated improved diagnostic accuracy in detecting dental caries, periodontal bone  loss, and periapical lesions. Additionally, AI has shown promising potential in treatment  planning and clinical decision support. However, limitations such as data heterogeneity,  limited clinical validation, and ethical concerns were reported.Conclusion: Artificial  intelligence demonstrates considerable potential to enhance diagnostic accuracy and clinical  efficiency in dentistry. Despite encouraging findings, further high-quality clinical studies  and standardized validation protocols are required before widespread integration of AI  technologies in routine dental practice.
Keywords: Artificial intelligence; dentistry; machine learning; deep learning; umbrella review; digital dentistry